Penyuluhan dan Pembuatan Sabun Cair Berbasis Minyak Goreng Bekas di Desa Trisnomaju, Kabupaten Pesawaran, Lampung Selatan - Nury, Dennis Farina; Auriyani, Wika Atro; Achmad, Feerzet; Luthfi, Muhammad Zulfikar (Politeknik ATI Padang, 2022)
Due to the many uses of cooking oil for household needs, it generates a huge residue called waste cooking oil or jelantah. Waste cooking oil can cause health and environmental problems. The conversion of waste cooking oil will help to reduce environmental damage. One of the conversion is making the waste cooking oil into valuable product as liquid soap. Liquid soap is made from Potassium hydroxide (KOH) reaction that produces salt (soap), water and glycerin. The saponification process was produced liquid soap using hydrolysis of waste cooking oil into fatty acids and glycerol in the KOH to hydrolyze. The waste cooking oil (jelantah) can ben converted into liquid soap by using the mixture of waste cooking oil, KOH solution, water and scent oil. This study aimed to educate the housewives about the problems of using waste cooking oil repeatly and to make liquid soap with a short training in Desa Trisnomaju, Kabupaten Pesawaran, Lampung Selatan. This activity consists of discussions, demonstrations and hands-on practice liquid soap. The results showed the the housewives were verry happy and enthusiastic during training. It can be concluded that the housewives are good and focus in making liquid soap, were increased in survey score from pretest to post test, 59,72% to 81,67%, respectively.